Afghanistan's Local War Building Local Defense Forces - Jones, Seth G. (RAND Corporation, 2010)
In Afghanistan, local communities have played a critical role in security, especially in rural areas. Afghan national security forces are important to the top-down strategy, but the Afghan government and NATO forces also need to leverage local communities to gain a complementary bottom-up strategy. This analysis discusses the viability of establishing local security forces in Afghanistan and addresses concerns about the wisdom of such policies.